Geographic Information Science 5th International Conference, GIScience 2008, Park City, UT, USA, September 23-26, 2008. Proceedings - Cova, Thomas J.; Miller, Harvey J.; Beard, Kate.; Frank, Andrew U.; Goodchild, Michael F.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2008)
This book constitutes the refereed proceedings of the 5th International Conference on Geographic Information Secience, GIScience 2008, held in Park City, UT, USA, in September 2008. The 24 revised full papers presented were carefully reviewed and selected from 77 submissions. Among the traditional topics addressed are spatial relations, geographic dynamics, and spatial data types. A significant number of papers deal with navigation networks, location-based services, and spatial information query and retrieval. Geo-sensors, mobile computing, and Web mapping rank among the important new directions.
Query Responsive Index Structures -- Refining Topological Relations between Regions Considering Their Shapes -- Noisy Road Network Matching -- Detecting Topological Change Using a Wireless Sensor Network -- Uncovering Hidden Spatial Patterns by Hidden Markov Model -- Modeling Herds and Their Evolvements from Trajectory Data -- New Data Types and Operations to Support Geo-streams -- Turn to the Left or to the West: Verbal Navigational Directions in Relative and Absolute Frames of Reference -- Effect of Neighborhood on In-Network Processing in Sensor Networks -- Similarity-Based Information Retrieval and Its Role within Spatial Data Infrastructures -- Geosensor Data Abstraction for Environmental Monitoring Application -- The 9?+?-Intersection: A Universal Framework for Modeling Topological Relations -- Decentralized Movement Pattern Detection amongst Mobile Geosensor Nodes -- A Framework for Sensitivity Analysis in Spatial Multiple Criteria Evaluation -- Reasoning on Spatial Relations between Entity Classes -- Identifying Maps on the World Wide Web -- Improving Localization in Geosensor Networks through Use of Sensor Measurement Data -- Simplest Instructions: Finding Easy-to-Describe Routes for Navigation -- Road Networks and Their Incomplete Representation by Network Data Models -- A Theory of Change for Attributed Spatial Entities -- Delineation of Valleys and Valley Floors -- Single-Holed Regions: Their Relations and Inferences -- Validation and Storage of Polyhedra through Constrained Delaunay Tetrahedralization -- Ontology-Based Geospatial Data Query and Integration.
Keywords: Computer science; Earth sciences; Data mining; Information storage and retrieval; Multimedia information systems; Computer Science; Data Mining and Knowledge Discovery; Earth Sciences, general; Information Systems Applications (incl. Internet).; Information Storage and Retrieval; Multimedia Information Systems; Electronic books